Accounting Learning Behavior in Project-Based Classroom: Method, Environment, Behavioral Control - Gainau, Paskanova Christi; Sijabat, Asiani; Leatemia, Senda Yunita; Basuki, Ferry Hendro (Jurnal Pendidikan Akuntansi (JPAK), 2025)
This study investigates the factors that influence students' learning behavior in a project-based accounting class. A quantitative approach was employed by distributing questionnaires to students after they participated in group projects in the Accounting Computerization course at the Faculty of Economics and Business, Pattimura University. The study collected data on students’ perceptions of the project-based classes they had undertaken. Multiple regression analysis was conducted using SPSS 28 as the data analysis tool. The results indicate that attitude does not influence accounting learning behavior. Furthermore, project-based learning methods, environment, and behavioral control have a significant influence on the learning behavior of accounting students. Project-based learning methods provide ample space for students to be directly involved in problem-solving, thereby increasing engagement, interaction, and collaboration with group members and instructors, and fostering positive learning behaviors. The strength of this influence is demonstrated by an R-squared value of 68.7%, which indicates that the influence between variables falls into the strong category. The better the learning environment and behavioral control, the more positive the learning behavior.